Practical Methods for Crack Length Measurement and Fatigue Crack Initiation Detection Using Ion-Sputtered Film and Crack Growth Characteristics in Glass and Ceramics - Deng, Gang; Nakanishi, Tsutomu (IntechOpen, 2011)
None